The Model of Administration Towards Excellence for School Administrators under Primary Educational Service Area Office in the Three Southern Border Provinces - Uma, Sutueroh; Suwanno, Phimpawee; Kao-ian, Jarunee; Buengacha, Suhairee (Al-HIKMAH Journal, 2024)
This research aimed to 1) study current condition and priority needs in administration towards excellence for school administrators under Primary Educational Service Area Office in the Three Southern Border Provinces, 2) develop the model, and 3) assess the model. The research process was divided into three phases. Phase 1: to study current condition and priority needs, collecting qualitative data through in-depth interviews using a semi-structured interview with nine school administrators, analyzing the content, and collecting quantitative data from 274 school administrators using needs questionnaire were proceeded. The data was analyzed for priority need index (PNI Modified). Phase 2: developing a focus group of five school administrators was executed and phase 3: assessing the model by 17 school administrators who were given the prestigious OBEC award over the past three years (2020-2022) through model assessment based on four aspects of Stufflebeam et al. (1994) evaluation model. The data was then analyzed for mean and standard deviation. The research findings showed that 1) the current condition of administration towards excellence for school administrators under Primary Educational Service Area Office in the three southern border provinces was at the highest level with priority need index (PNIModified), top 3 rankings including Measurement, Analysis and Knowledge Management, Results, and Strategy, 2) the model consisted of four components including principles of model, objectives of model, procedures of model, and factors/conditions for success, and 3) the assessment result of the model was overall at the highest level.